Augmented Brain Infiltration and Activation of Leukocytes After Cerebral Ischemia in Type 2 Diabetic Mice - Zhang, Fang; Zhao, Qiuchen; Jiang, Yinghua; Liu, Ning; Liu, Qiang; Shi, Fu-Dong; Hao, Junwei; Xu, Yun; Lo, Eng H.; Wang, Xiaoying (Frontiers in Immunology, 2019)
Stroke patients with diabetes suffer from higher mortality rate and worsened neurological outcome. However, the responses of immune system to cerebral ischemia in the setting of diabetes remain poorly understood. In this study, we investigated the temporal profile of leukocyte mobilization and brain infiltration following distal middle cerebral artery occlusion (dMCAO) in db/db mouse model of type 2 diabetes and its db/+ normoglycemic controls. We found a significant increase of brain-infiltrating CD4+ T cell at day 3 after dMCAO, and a delayed and dramatic increase of brain-infiltrating neutrophils, CD4+ T cells, CD8+ T cells and B cells at day 7 after dMCAO in db/db mice versus db/+ controls. Leukocyte subsets in the circulation and spleen were also measured, however, there was no significant difference between non-diabetic and diabetic groups. Furthermore, we identified an increased expression of activation marker CD69 in brain-infiltrating neutrophils, CD4+ T and CD8+ T cells, and IFN-γ in brain-infiltrating CD4+ T cells in db/db mice at day 7 after dMCAO. Our findings for the first time demonstrate a delayed and sustained augmentation of brain infiltration and activation of neutrophils and lymphocytes in type 2 diabetic mice after brain ischemia. These altered immune responses might contribute to the increased brain damage and worse neurological outcomes of diabetes stroke, which warrants further investigation.